Determinants of Smoking Behavior among High School students in Jahrom - A Khalooei; A Jafarzadeh; K Rahmanian (Tehran University of Medical Sciences, 2010)
Background and Aim: Tobacco use is a major contributor to deaths from chronic diseases, one which begins during adolescence. The aim of this study was estimate the smoking prevalence and examines the determinants of smoking behavior among high school students in Jahrom, Iran.Materials and Methods: This study is a cross-sectional survey that was done in Spring, 2007 in Jahrom. Students were selected by multistage sampling. An anonymous, valid, reliable, self administered questionnaire was filled in by all selected students presented at the day of the survey. Chi-square, student - t and logistic regression test was used to examine the determinants of smoking behavior .Results: The prevalence of smoking among high school and pre-college students was 9.4% and 12.7% respectively. 53% of high school and 88% of pre-college students received cigarette their first time from their friends.The most powerful determinant of smoking among students of both school levels was sex.Discussion and Conclusion: Effective smoking prevention programmers should take into account the dominant influence of peers and family members and also its focuss on the age of onset and maintenance of smoking behavior.